My bike - Jakob, Donna; Davis, Nelle (New York : Hyperion Books for Children, 1994)
A boy learns the difference between yesterday when he could not ride his bike and today when he leads all the bicyclists.
School Library Journal
Publisher's Weekly
2.3
K-3
Keywords: Bicycles and bicycling -- Fiction; Time -- Fiction; Bicycles -- Fiction; Time -- Fiction